Business in Britain in the twentieth century - Coopey, R. (Richard); Lyth, Peter J. (Oxford : Oxford University Press, 2009)
This collection of fresh, incisive scholarship, by some of the leading business historians, critically examines the nature of economic recovery in Britain in recent years. Covering the key issues for business history in this period, this overview confronts the traditional literature's conclusions and simplistic explanations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Great Britain -- Economic conditions -- 20th century; Great Britain -- Economic policy -- 20th century; Great Britain -- Commerce -- History -- 20th century